Contributions Concerning the Oscilloscopic Method, for checking the Clock-Hour Figure of the Vector Group of a Electric Transformer - Prodan, C.; Cernomazu, D.; Chatziathanasiou, V. (Elektronika ir Elektrotechnika, 2013)
The wiring diagrams, the vector groups and the clock hour figures of the vector group, are interesting aspects for the design, the manufacture and the operation of the transformers, especially for the power transformers. The parallel operation of the transformers, the unbalanced load which occurs at the running with load, and the study of the phenomenon produced at the transformers magnetization represent interesting aspects directly related to the connections field of the vector groups and the clock hour figures of the vector group. The paper presents the authors' contributions to two of the methods for determining the clock hour figure of the vector group, namely the achievement of a device for identifying the clock-hour figure for the three-phase transformer, built on the principles of the oscilloscopic method and the compensation method. The solution presented in the paper leads to a considerable simplification of the oscilloscopic method, which, even if it bears the name used in the literature, does not use an oscilloscope, device considered expensive and complicated; by using the proposed solution we obtain a higher precision of the measurements, limiting the risk of errors, which can occur in case of small phase displacements. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.1929